FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA KUNJUNGAN K4 IBU HAMIL DI WILAYAH KERJA PUSKESMAS KUNDI KABUPATEN BANGKA BARAT : Misyati S Asmarudin, Novi Haryanti (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
Pregnancy and childbirth are natural events, but they are often accompanied by risks in the form of complications for both the mothers and the babies. The complications that often occur are postpartum hemorrhage, eclampsia and infection. Based on data from the Public Health Center Kundi, the coverage of K4 visits for pregnant women in 2018 were 178 mothers (97.27%), in 2019 were 154 mothers (93.90%) and in 2020 were 148 mothers (89.70%). This study aims to determine the related factors towards the low rate of four times antenatal (K4) visits to pregnant women in the work area of Public Health Center Kundi, West Bangka Regency in year 2020. This research employs a cross sectional design, with the total population of entire pregnant women/maternal mothers in the work area of the Public Health Center Kundi in 2020 with the total number of 165 mothers. And it takes sample size of 70 pregnant women. The obtained data are then analyzed using Univariate and Bivariate analysis with Chi-square statistic test. The result of data analysis shows that the related factors towards the low rate of K4 visits at the Public Health Center Kundi in 2020 were lack of knowledge (p=0.008), Low education (p=0.009), Less attitude (p=0.002), High parity (p=0.000), Pregnancy distance is less (p=0.000,), and Husband's support is Less (p=0.000). Whereas the factors that are not related to the low rate of K4 visits at the Public Health Center Kundi in 2020 are lack of work (p=0.086) and less Health Officer support (p=1.000,). It is recommended that pregnant women whose visits have not been completed are expected to improve their ANC visits and provide information to their husbands about the importance of husband's support for regular Antenatal Care visits so that they can detect early if complications and emergencies occur